FORMULASI SEDIAAN CREAM DAN UJI AKTIVITAS ANTIBAKTERI PADA EKSTRAK ETANOL KOMBINASI KULIT PISANG (Musa paradisiaca) DAN KULIT NANAS (Ananas comosus) TERHADAP BAKTERI PENYEBAB JERAWAT Propionibacterium acnes - Pintata Sembiring (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
Background: Acne vulgaris is a chronic inflammatory skin disease with a complex pathogenesis, involving sebaceous glands, follicular hyperkeratosis, bacterial overgrowth, immune and inflammatory responses. Objective: This formulate the ethanol extract of banana peel and pineapple peel into cream preparations and to test the effective antibacterial activity of the combination of banana peel and pineapple peel ethanol extract cream against Propionibacterium acnes. Methods: This research was conducted experimentally with maceration extraction using 70% ethanol as solvent. Acne cream is made with a concentration ratio between (Banana peel: Pineapple peel) namely F1 (Cream Base), F2 (5%:15%), F3 (7.5%:12.5%), F4 (10%:10% ), F5 (12.5%:7.5%), F6 (15%;5%), F7 (20%:0%) and F8 (0%;20%). Then, the physical stability test was carried out in the form of organoleptic test, viscosity test, pH test, homogeneity test, spreadability test and cream type test. Followed by testing the bacteria Propionibacterium acnes in Na media. Results: The antibacterial activity test on F3 showed that the diameter of 20.18 mm was relatively larger than F1 of 0mm, F2 of 18.63 mm, F4 of 18.38 mm, F5 of 16.48 mm, F6 of 18.28 mm, F7 of 13.91 mm and The F8 is 16.11 mm. Conclusion: Cream preparations from formula 1 to formula 8 the cream stability organoleptic test, viscosity test, pH test, homogeneity test, test spreadability and cream type test. The cream preparation in formula 3 has the widest diameter for antibacterial activity compared to other formulas.